Internet safety - Herrington, Lisa M. (New York : Children's Press, 2013)
Introduces young readers to ways to be safe and responsible while using the Internet.
Includes index.
2.8
Preschool
Preschool
Keywords: Internet and children -- Juvenile literature; Internet -- Safety measures -- Juvenile literature; Safety education -- Juvenile literature; Internet; Internet -- Safety measures; Safety; Internet; Internet -- Safety measures; Safety education; Readers (Elementary).